Forensic psychiatry at a tertiary care hospital in Faisalabad: an Audit from 2015-2018 - Siddique, Irum; Biag, Muhammad Nasir; Haider, Nighat; Dogar, Imtiaz Ahmad (Journal of Pakistan Psychiatric Society, 2019)
Forensic psychiatry at a tertiary care hospital in Faisalabad: an Audit from 2015-2018.